Human-computer interaction. 17th International Conference, HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, Proceedings /: 17th International Conference, HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, Proceedings. Design and evaluation : Part I, (2015) - Unknown
No abstract available